2014
DOI: 10.1074/jbc.m113.509158
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox Transcription Factor VentX Regulates Differentiation and Maturation of Human Dendritic Cells

Abstract: Background:The transcriptional regulation of human dendritic cells (DCs) differentiation and maturation remains incompletely understood. Results: VentX knockdown impaired DCs differentiation and maturation whereas VentX overexpression counteracted the inhibitory effects of corticosteroid on DC activation. Conclusion: VentX is critical for DCs differentiation and maturation. Significance: VentX may be a novel target to modulate DCs functions and manage inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…To explore the potential clinical relevance of the findings, we performed sequence homology search and functional analysis, which led to the identification of human homeobox protein VentX as a human homolog of Xom 12 , 13 . We found that VentX is primarily expressed in hematopoietic cells and controls proliferation and differentiation of hematopoietic cells from early ontogenesis to terminal differentiation 12 , 14 16 . Interestingly, comparative genomic studies showed that VentX is preserved in primates and human but lost in mice since the evolutionary divergence of rodent and primate lineages 17 .…”
Section: Introductionmentioning
confidence: 89%
“…To explore the potential clinical relevance of the findings, we performed sequence homology search and functional analysis, which led to the identification of human homeobox protein VentX as a human homolog of Xom 12 , 13 . We found that VentX is primarily expressed in hematopoietic cells and controls proliferation and differentiation of hematopoietic cells from early ontogenesis to terminal differentiation 12 , 14 16 . Interestingly, comparative genomic studies showed that VentX is preserved in primates and human but lost in mice since the evolutionary divergence of rodent and primate lineages 17 .…”
Section: Introductionmentioning
confidence: 89%
“…C. elegans ceh-51 encodes a homeodomain-containing transcription factor that functions in mesoderm (Broitman-Maduro et al 2009). In OL1, it was called as the ortholog of VENTX, a homeodomain transcription factor that functions in the human mesodermal derivatives of the myeloid lineage (Rawat et al 2010;Wu et al 2011Wu et al , 2014Gao et al 2012). In OL2, four other C. elegans homeodomain (ceh) genes are now called as VENTX orthologs, underscoring how adjustments to the prediction programs may lead to shifts in which possible paralogs in C. elegans are called as orthologs of human genes.…”
Section: The Legacy Gene Setmentioning
confidence: 99%
“…Mechanistically, we found that, similar to Xom, VentX binds to LEF/TCFs through its homeobox domain and disrupts the interaction between β‐catenin and LEF/TCFs . Consistent with its role as a canonical Wnt antagonist, recent studies from our laboratory showed that VentX plays essential role in proliferation and differentiation of hematopoietic and immune cells . As such, further exploration of the regulatory mechanisms of ubiquitin‐mediated proteolysis during early embryogenesis is likely to bring novel knowledge that is broadly implicated in immunity, cancer biology, and regenerative medicine.…”
Section: Discussionmentioning
confidence: 55%